Severe Growing-Up Phobia, a Condition Explained in a 14-Year-Old Boy - Perales-Blum, Laurencia; Juárez-Treviño, Myrthala; Escobedo-Belloc, Daniela (Case Reports in Psychiatry, 2014)
We present the clinical case of a 14-year-old boy with gerascophobia or an excessive fear of aging, who felt his body development as a threat, to the point where he took extreme measures to stop or otherwise hide growth. He had a history of separation anxiety, sexual abuse, and suffering bullying. He presented with anxious and depressive symptoms and food restriction, criticized his body image, had negative feelings towards the maturation process, suffered at the thought of being rejected, and was preoccupied with certain physical characteristics. We conducted an analysis of biological, psychological, and environmental factors and their possible interactions and established treatment with psychotherapy and fluoxetine. Because of the favorable results, this approach could be considered a good option in such cases.